Enhanced technique for prediction of Z-R relationship in tropical region - Aziding, Khairunnisa; Badron, Khairayu; Basri, Atikah Balqis; Ismail, Ahmad Fadzil; Ahmad, Yasser Asrul (IOP Publishing, 2023)
Abstract. Over the years, research has been directed to investigate radar as potential tools for estimating rain. The radar reflectivity is measured by comparing the location of the rain gauge and the associated vertical path at certain altitude. The latitude and longitude of the rain gauge is identified to pinpoint the exact associated location by using Rainbow® 5 meteorological software. In this work, radar reflectivity was estimated by using S-band Terminal Doppler Weather Radar (TWDR) data at Malaysian KLIA radar station. The rain gauge is owned by Malaysian Department of Irrigation and Drainage (DID) at several locations within the vicinity of the radar. A technique to estimate the Z-R relationship by using radar reflectivity information and rainfall rate from rain gauge values is demonstrated in this article. Comparisons between radar reflectivity and actual rain gauge measurement is presented. Preliminary findings using available Z-R relation shows similar values with the actual measurement and suitable to be used in tropical climate country such as Malaysia.